THE LATE HELLENISTIC AND EARLY ROMAN FINE POTTERY FROM THE SANCTUARIES OF DIOMEDES IN DALMATIA - Miše, Maja; Šešelj, Lucijana (Rei Cretariae Romanae Fautorum Acta, 2024)
Archaeological research on the island of Palagruža and at cape Ploča has given extensive material evidence of the cult of Diomedes in the Adriatic. The excavations revealed a large quantity of pottery fragments. The majority of the pottery fragments belong to fine votive pots. Some pots are bea incised graffiti with the name of Diomedes, attested about 40 times.